PEMANFAATAN MINYAK JELANTAH SEBAGAI PENGGANTI BAHAN BAKAR SOLAR DALAM UPAYA MENURUNKAN DAMPAK GAS RUMAH KACA (STUDI KASUS: KOTA PADANG, SUMATERA BARAT) - Azhari, Fuad; Miefthawati, Nanda Putri (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
Padang City with the largest consumption of diesel fuel in West Sumatra Province will have an impact on fuel availability and global warming which increases the effects of greenhouse gases such as carbon emissions. The use of used cooking oil as a biodiesel substitute for diesel fuel can reduce dependence on diesel consumption and reduce the impact of greenhouse gases. The purpose of this study is to calculate the potential of biodiesel from used cooking oil and analyze the impact of greenhouse gases produced. The transesterification method simulated in the Superpro Designer application is able to produce 314,732.55 liters of biodiesel per year with a density of 875.34 Kg/m3 at a temperature of 35℃. The calculation of carbon emissions refers to the IPCC Guidelines 2006 equation showing a decrease in carbon emissions produced by 279.75 tons of CO2 per year. The results of this study indicate that the biodiesel from used cooking oil obtained has met the Indonesian National Standard (SNI) and the use of biodiesel from used cooking oil can reduce the impact of greenhouse gases from carbon emissions.Keywords: Solar, Used Cooking Oil, Biodiesel, Greenhouse Gases